Analysis of the Utilization of Hydroponic Media in Welsh Onion Cultivation (Allium fistulosum L.) - Gloria Sirait; Irving Josafat Alexander; Ramlan Silaban (Fakultas Sains dan Teknologi, UIN Walisongo Semarang, 2023)
The food crisis is a condition when acute food hazards and net malnutrition increase sharply. One reason is due to a slowdown in food production. In 1627, a new farming method was known, called hydroponics, namely the method of growing with the help of water. After further investigation, it was found that the cultivation method with water will eventually produce plants that are as good as plants grown using soil media. Therefore, this research will explore the benefits of using hydroponic media in leek cultivation. In this study, there were two containers, the first container was not subject to the application of pesticides, while the second container was watered with onion peel vegetable pesticides twice a week. The results of the leek planting experiment in the hydroponic system and media showed that the maximum height achieved by the leek plants tested was as high as 22.8 cm, and only 3 out of 17 total plants died.